Competencies based learning of musical language students from Art High Schools in Ecuador - Rivas Chávez, Nelly Lourdes Alexandra; Jaramillo Carrillo, Patricio Giovanny; Mussó Mujica, Luis Carlos (Transformación, 2024)
Objective: The article explores the contribution of competency-based learning in the area of musical language for the benefit of the students of art high schools of Ecuador. Methods: The authors rely on the qualitative-quantitative descriptive method. The researchers attempted to reveal how Competency-based learning contributes to the strengthening of school performance in the area of musical language during the 2016-2017 school year. Results: The findings are the description of the teaching strategies used and the features that characterize the learning results derived from a competency-based approach in the area of musical language, as a solution to the learning former difficulties. Conclusions: The use of inappropriate strategies in the direction of the learning process has led to the predominance of mechanic learning. This situation could be transformed by training the teachers in introducing a competency-based learning approach.